Prevalence of sarcopenia in community-dwelling older people in the UK using the European Working Group on Sarcopenia in Older People (EWGSOP) definition: findings from the Hertfordshire Cohort Study (HCS). - Patel, H; Syddall, H; Jameson, K; Robinson, S; Denison, H; Roberts, H; Edwards, M; Dennison, E; Cooper, C; Aihie Sayer, A (2013)
INTRODUCTION: sarcopenia is associated with adverse health outcomes. The aim of this study was to describe the prevalence of sarcopenia in community-dwelling older people in the UK using the European Working Group on Sarcopenia in Older People (EWGSOP) consensus definition. METHODS: we applied the EWGSOP definition to 103 community-dwelling men participating in the Hertfordshire Sarcopenia Study (HSS) using both the lowest third of dual-energy X-ray absorptiometry (DXA) lean mass (LM) and the lowest third of skin-fold-based fat-free mass (FFM) as markers of low muscle mass. We also used the FFM approach among 765 male and 1,022 female participants in the Hertfordshire Cohort Study (HCS). Body size, physical performance and self-reported health were compared in participants with and without sarcopenia. RESULTS: the prevalence of sarcopenia in HSS men (mean age 73 years) was 6.8% and 7.8% when using the lowest third of DXA LM and FFM, respectively. DXA LM and FFM were highly correlated (0.91, P < 0.001). The prevalence of sarcopenia among the HCS men and women (mean age 67 years) was 4.6% and 7.9%, respectively. HSS and HCS participants with sarcopenia were shorter, weighed less and had worse physical performance. HCS men and women with sarcopenia had poorer self-reported general health and physical functioning scores. CONCLUSIONS: this is one of the first studies to describe the prevalence of sarcopenia in UK community-dwelling older people. The EWGSOP consensus definition was of practical use for sarcopenia case finding. The next step is to use this consensus definition in other ageing cohorts and among older people in a range of health-care settings.